Intestinal Parasitic with Relation to Socio-Economic Status of Jalari and Kumal Communities in Lekhnath Municipility, Kaski, Nepal - Jamerkattel, Madan Prasad; Ghimire, T. R. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Intestinal parasites; Socioeconomic status DOI: 10.3126/jnhrc.v5i2.2451 Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 13-20